Developmental Outcome in Children with Malnutrition - Chattopadhyay, Nandita; Saumitra, Masani (Journal of Nepal Paediatric Society, 2016)
Background: Developmental challenges and malnutrition are two major childhood health problems in the developing world and malnutrition is a major risk factor for poor development, which can, ultimately, lead to developmental challenges with life-long implications, affecting the individual, the family and the society at-large. Materials and Methods: We searched PUBMED & COCHRANE REVIEW databases, published documents from WHO, UNICEF, UNDP and the World Bank and citations thereof, for relevant literature on brain development and malnutrition, dietary supplementation and brain development. Results: Effect of nutrition on the developing brain has been thoroughly studied and established. Undernutrition, particularly during fetal and 1st two years of postnatal life, is a major risk factor for poor neuro-development, leading to motor, cognitive and speech delay, as well as behavioral problems and learning disabilities. Macro and micro-nutrients, like proteins, Iron, Iodine, Zinc, vitamins-B, C and D, choline and essential fatty acids are essential for proper brain development. Supplementation of pregnant and lactating mothers, infants and toddlers with multiple micronutrient, specially Iron, Iodine, Vitamins B12 and Folate and choline has been found beneficial, particularly among the vulnerable population. Conclusion: Dietary supplementation for pregnant and lactating mothers, infants and toddlers along with a congenial socio-emotional environment and cognitive stimulation from an early age can go a long way to help the child at-risk attain his developmental potential. J Nepal Paediatr Soc 2016;36(2):170-177.